Detection of the unknown components of the oral microflora of teeth with periapical radiolucencies in a Turkish population using next-generation sequencing techniques - İRİBOZ, EMRE (WILEY, 2018)
Aim To detect the unknown components of the oral microbiome and the effects of root canal treatment in a Turkish population and to evaluate the changes in microbial diversity in the root canals before and after treatment. Methodology Results Single-rooted central and lateral maxillary incisors with one canal were chosen from 20 patients. Baseline samples of intact intracanal microbiota were collected from 20 root canals of permanent teeth with necrotic pulps using sterile paper points. After root canal preparation, the root canals were filled with a calcium hydroxide paste for 7 days. Calcium hydroxide was removed from root canal with 2.5% sodium hypochlorite and 17% EDTA using passive ultrasonic irrigation (PUI). A second bacteriologic samples were taken with sterile paper points prior to root filling. The samples were processes with DNase-I treatment using next-generation sequencing (NGS). Reduction in bacterial numbers during root canal treatment was evaluated using real-time quantitative PCR (qPCR). All statistical analyses were conducted using the MINITAB 17 software (Minitab Ltd. Co., Coventry, UK). A one-sample t-test was used to analyse the data. Statistical significance was accepted at P Relative abundances of Mycoplasma sp., Paludibacter sp., Tannerella sp., Prevotella spp. and an uncultured species from the order Bacteroidales decreased with root canal preparation and medication (98.7%, 99.8%, 98.8%, 97.7% and 99.3%, respectively), whilst the relative abundances of Methylobacterium sp., Corynebacterium sp. and Streptococcus infantis increased (93.1%, 94.8% and 99.4%, respectively). Considerable numbers of Streptophyta species were detected before and after treatment. The ratio of Agrobacterium sp. in the treated teeth community and the ratio of order Streptophyta in the infected canals had negative correlations with the success of bacterial elimination. Conclusions The combination of NGS and qPCR techniques resulted in detection of previously unknown components of the oral microbiome and the effects of root canal treatment on their relative abundance in a Turkish population.
Keywords: apical periodontitis; bacterial microflora; next-generation sequencing; quantitative polymerase chain reaction; Turkish population; ROOT-FILLED TEETH; ENDODONTIC INFECTIONS; CALCIUM HYDROXIDE; BACTERIA; DNA; METHYLOBACTERIUM; MICROORGANISMS; AGROBACTERIUM; CANALS; INSTRUMENTATION